Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.3.rs-15675/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stigma for Common Mental Disorders in Racial Minorities and Majorities A Systematic Review and Meta-Analysis

Abstract: Background There is a strong stigma attached to mental disorders preventing those affected from getting psychological help. The consequences of stigma are worse for racial and/or ethnic minorities who often experience other social adversities such as poverty and discrimination within policies and institutions. This is the first systematic review and meta-analysis summarizing the evidence on the impact of differences in mental illness stigma between racial minorities and majorities.Methods This systematic revie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…Wireless penetration and digital literacy have been suggested as potential explanations, although widespread telemedicine adoption during the pandemic may improve acceptability and comfort over time. [57][58][59] Prior telemedicine studies in mental health have been limited to a single payer, a particular institution or practice, or certain populations, such as veterans, rural beneficiaries, or incarcerated individuals. 56,[60][61][62][63][64] These have established the non-inferiority in outcomes and patient satisfaction of more common provider-driven telemental health models, such as clinic-basedvideoconferencing, electronic consultation, or collaborative models in the assessment or treatment of specific behavioral health conditions, as compared to inperson visits.…”
Section: Discussionmentioning
confidence: 99%
“…Wireless penetration and digital literacy have been suggested as potential explanations, although widespread telemedicine adoption during the pandemic may improve acceptability and comfort over time. [57][58][59] Prior telemedicine studies in mental health have been limited to a single payer, a particular institution or practice, or certain populations, such as veterans, rural beneficiaries, or incarcerated individuals. 56,[60][61][62][63][64] These have established the non-inferiority in outcomes and patient satisfaction of more common provider-driven telemental health models, such as clinic-basedvideoconferencing, electronic consultation, or collaborative models in the assessment or treatment of specific behavioral health conditions, as compared to inperson visits.…”
Section: Discussionmentioning
confidence: 99%
“…As members of minority groups, MARs and SGM also have in common that they are susceptible to differential treatment in the societies in which they live [ 82 , 83 ] and are often confronted with stigmatization, prejudice, and discrimination [ 83 , 84 , 85 , 86 , 87 , 88 ]. Stigma, discrimination, and prejudice emerge when individuals and groups are ‘othered’.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Stigma is another factor that affects patients’ likelihood of seeking out treatment. 16 A meta-analysis performed in 2020 concluded that minorities have a significantly increased stigma toward mental health illness compared to White communities. 16 It is important to note that the studies reviewed in this paper have examined both depressive and anxiety disorders together while our study focuses only on treatment of anxiety disorders.…”
mentioning
confidence: 99%